Beyond profit and self-interest : economics with a broader scope - Gassler, Robert Scott (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2004)
This book attempts to reformulate existing orthodox economic theory in order to improve its conversation with disciplines that have traditionally been seen as the domain of political scientists,sociologists,psychology and even biologists, and to fit economics into the broader scheme of social science theory.
Includes bibliographical references and index.
Keywords: Economics